A Study of Fractal Deep-Hole Blasting and Its Induced Stress Behavior of Hard Roof Strata in Bayangaole Coal Mine, China - Jianping Zuo; Zhengdai Li; Shankun Zhao; Yunqian Jiang; Haiyan Liu; Maohong Yao (Advances in Civil Engineering)
The phenomena of strong pressure occurrences have been observed many times in the #311103 working face of the Bayangaole Coal Mine. Deep-hole blasting measures were used to relieve the pressure in order to decrease the danger levels of these strong pressure occurrences on the working face. The blasting layouts proposed in this study differed from the conventional blasting layouts of a “straight-line” design by instead utilizing “triangular-fractal” and “deep-shallow-fractal” for the purpose of successfully driving the explosive efficiency and enlarging the roof-blasting range. The fractal dimension of the “triangular-fractal” blasting layout was calculated as 1.1274. The fractal dimension of the “deep-shallow-fractal” was calculated to be 1.556. The fractal dimensions of both improved layouts were found to be larger than that of the “straight-line” blasting layout (1.0). In addition, the Mises stress evolution and the changed trend of the effective stress and strain of the observation points around the hole of the three layouts are analyzed and compared by LS-DYNA numerical simulation software. The results indicated that the “deep-shallow-fractal” blasting layout had the most effective blasting effects, followed by the “triangular-fractal” blasting layout. It was determined that the traditional “straight-linear” blasting layout had the least effective blasting effects of the three examined layouts. In summary, the implementations of the improved fractal blasting layouts in this study were found to be conducive to the enhancement of the blasting effects.